PALLADIUM, PLATINUM AND GOLD DISTRIBUTION IN PORPHYRY CU ± MO DEPOSITS OF RUSSIA AND MONGOLIA - Sotnikov V.I.; Berzina A.N.; Economou-Eliopoulos M.; Eliopoulos D.G. (My University, 2001)
The porphyry Cu–Mo deposits in the southern Siberian craton and Northern Mongolia including subduction-, collision-, and rift-related igneous series of early Paleozoic to Mesozoic age, are all characterized by varying crustal contribution to their parent magmas and the presence of explosive breccias. Precious metal and associated element contents are reported for mineralized samples, sulphide concentrates, and chalcopyrite–molybdenite flotation concentrates from porphyry Cu±Mo intrusions of Russia (Sora, Aksug and Zhireken) and Mongolia (Erdenetiun-Obo). Average PGE contents in rocks are 17 ppb Pd and 22 ppb Pt in the Aksug deposit, 13 ppb Pd and <10 ppb (detection limit) Pt in the Sora, 14 ppb Pd and 21 ppb Pt in the Erdenetuin-Obo and 18 ppb Pd and 28 ppb Pt in the Zhireken deposit. Average gold content in rocks is 61 ppb in the Aksug deposit, 17 ppb in the Sora, 21 ppb in the Erdenetuin-Obo, and 30 ppb in the Zhireken deposit. The highest average 2.3 ppm Ag was recorded in the rocks of the Sora deposit. In general, the precious metal distribution in the studied deposits has no apparent relationship with the alteration types. The molybdenum content in rocks ranges between <1 and 128 ppm Mo in the Aksug deposit, from <1 to 5400 ppm Mo in the Sora deposit, from 2 to 755 ppm Mo in the Erdenetuin-Obo deposit, and from 3 to 1530 ppm Mo in the Zhireken deposit. The average copper content in rocks is 1540 ppm in the Aksug deposit, 460 ppm in the Sora deposit, 1460 ppm in the Erdenetuin-Obo deposit, and 220 ppm in the Zhireken deposit. The Cu–Mo ratios are highest in the Aksug and Erdenetuin-Obo deposits and lowest in the Sora and Zhireken deposits. The correlation matrix for selected major and trace element data on mineralized samples and sulphide concentrates (34 samples) indicates that precious metals are associated with either chalcopyrite or molybdenite. Copper shows a strong positive correlation with Au and Pd (r≥+0.91) while Mo shows a strong positive correlation with Pt (r=+0.98). In addition, Mo exhibits a strong positive correlation with W (r=+0.94). An interelement positive correlation between precious metals is 0.57 (Ag–Au). The Pd and Pt contents of both chalcopyrite and molybdenite in flotation concentrates are low, varying from 9 to 83 ppb Pd and from <10 to 110 ppb Pt. The highest values recorded are 924 ppb Pd in sulphide concentrates from the Aksug deposit, and 684 ppb Pd and 299 ppb Pt in sulphide concentrate from breccia of the Zhireken deposit. The highest gold content, 5450 ppb Au, is in chalcopyrite flotation concentrate from the Aksug deposit, whereas in the majority of concentrates the gold content is in the order of a few hundreds parts per billion. The relatively low contents and limited variation of the precious metal contents in the individual deposits of Russia and Mongolia point to the essential role of the composition of the source and composition of parent magmas.
Keywords: Paleozoic; Mesozoic; Палеозой; Mesozoic; Paleozoic; Мезозой